"Fili d'oro": Literature, painting, and blindness in D'Annunzio's Notturno. (August 2017) - Mirabile, Andrea
This article analyzes the relationships between literature and the arts in D'Annunzio's Notturno . The verbal and the visual constantly intersect in the poet's corpus. Nevertheless, the Notturno is unique: according to the narrator, he composes the text during a period of semi-blindness caused by a war-related accident. Consequently, the protagonist is unable to see his favorite works of art, which are described through the filters of memory, desire, and imagination. D'Annunzio's nocturnal ekphrasis blends wake and dream, asceticism and eroticism, narrative linearity and poetical fragmentation. Vision and writing deconstruct their own conventional separations: the elements of each form mingle in a dimension that reflects simultaneously the influence of the Decadent age and the birth of Modernism. Despite the scarce scholarly attention devoted to the Notturno outside the borders of Italy, D'Annunzio's text anticipates the current debates on the aporias of sight (Derrida), the ambiguous temporality of the visual arts (Didi-Huberman), and the contradictory distinction between 'internal' and 'external' vision (Belting).